2019
DOI: 10.1001/jamanetworkopen.2019.11120
|View full text |Cite
|
Sign up to set email alerts
|

Effect of MyTeen SMS-Based Mobile Intervention for Parents of Adolescents

Abstract: Key PointsQuestionIs a brief parenting program delivered solely via text message effective in improving parental competence and mental health literacy in parents of adolescents?FindingsIn this randomized clinical trial of 221 parents and caregivers, significant group differences were observed between those receiving the text-messaging intervention and the control group. Participants who received the text-messaging program reported higher levels of parental competence, improved knowledge of help seeking, improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(79 citation statements)
references
References 35 publications
2
72
5
Order By: Relevance
“…Studies from other parts of the world have evaluated SMS-based mobile interventions for parents of adolescents and suggest this to be an effective and feasible method to provide evidence-based information to parents, who cannot be easily reached. 10 Keeping these issues in mind, this study was conceived to provide continuity of care and also to utilize the availability of parents at home to improve the outcome of the children with ADHD.…”
Section: Introductionmentioning
confidence: 99%
“…Studies from other parts of the world have evaluated SMS-based mobile interventions for parents of adolescents and suggest this to be an effective and feasible method to provide evidence-based information to parents, who cannot be easily reached. 10 Keeping these issues in mind, this study was conceived to provide continuity of care and also to utilize the availability of parents at home to improve the outcome of the children with ADHD.…”
Section: Introductionmentioning
confidence: 99%
“…Two other studies found a smaller difference in PACS scores between the intervention and control group (e.g. 2.57 [ 41 ] and 2.21 [ 42 ]). However, both of these intervention studies entailed minimal in-person contact and sending prompts to the parents by mobile phone.…”
Section: Methodsmentioning
confidence: 99%
“…The 18 included studies were published between 1988 and 2019. The majority were conducted in the United States [29,42e 52], and the rest were conducted across a variety of countries, including Australia [53,54], New Zealand [28], Japan [55], Canada [56], and England [57]. Three of the studies were cohort studies, four were quasi-experimental, and 11 were RCTs.…”
Section: General Overviewmentioning
confidence: 99%
“…Of the studies that provided information about which parent participated [28,29,46,50,51,53e56], only one had an equal number of mothers and fathers [55], and in most studies, most participating parents were mothers (64%e100%). The focus of interventions was on changing parents' help-seeking behavior [42e49,55e57], help-seeking intentions [29,54], knowledge of help-seeking options [28], attitudes toward seeking help and help-seeking behaviors [50,51], knowledge of help-seeking options and attitudes toward seeking help [53], and attitudes and intentions toward seeking help [52]. Of the studies, nine found a significant increase in help-seeking [28,42,44,46e49,51,55], five found no significant increase [29,43,45,52,54], and four studies [50,53,56,57] found mixed results.…”
Section: General Overviewmentioning
confidence: 99%
See 1 more Smart Citation